A Substance P (SP)/Neurokinin-1 Receptor Axis Promotes Perineural Invasion of Pancreatic Cancer and Is Affected by lncRNA LOC389641. (12th May 2022) - Ji, Tengfei; Ma, Keqiang; Wu, Hongsheng; Cao, Tiansheng
Abstract : Perineural invasion (PNI) is considered to be a main reason for the poor prognosis of pancreatic cancer. In the present study, we analyzed the roles of substance P (SP)/neurokinin-1 receptor (NK-1R) and lncRNA LOC389641 in pancreatic cancer PNI. Pancreatic cancer cell lines BxPC-3 and MIAPaCa-2 were cocultured with SH-SY5Y cells and then stimulated with SP to simulate the in vivo influence of ganglia on pancreatic cancer. The BxPC-3 and MIAPaCa-2 cells were transfected with a neurokinin-1 receptor (NK-1R) overexpression vector, NK-1R silencing vector, LOC389641 overexpression vector, or LOC389641 silencing vector, respectively. The proliferative abilities of BxPC-3 and MIAPaCa-2 cells were assessed using the cell counting kit-8 and 5-ethynyl-2 ′ -deoxyuridine (EdU) assays. Wound-healing and Transwell assays were performed to determine the migration and invasion abilities of the cells. When SP was added to the coculture system, it positively regulated cancer cell proliferation, migration, and PNI and significantly activated the NK-1R/Akt/NF- κ B signaling pathway. Incubation with 100 nmol/L SP for 24 h was selected as the optimal condition for treatment. The activated NK-1R positively regulated the proliferation, migration, and invasion of pancreatic cancer cells. However, the levels of lncRNA LOC389641 and tumor necrosis factor receptor SF10A (TNFRSF10A) mRNA in BxPC-3 and MIAPaCa-2 cells were not affected by SP treatment. Overexpression or silencing of LOC389641 changed the effect of SP stimulation on pancreatic cancer PNI. When taken together, these results revealed that SP/NK-1R and LOC389641 promoted the progression of pancreatic cancer PNI. Moreover, we found that pancreatic cancer PNI promoted by the SP/NK-1R axis could be blocked by the TNFRSF10A/NF- κ B pathway mediated by LOC389641.